2021
DOI: 10.25107/cis-v6-id3307
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stone Disease of Non Gouty Origin in 264 Popes (34-2005 AD): A Historical Review

Abstract: A total of 11 non-gouty popes out of 264 (4.1%) died of kidney stones (very probably calcium stones) between the years 34-2005 AD. The prevalence of kidney stones was lower than expected on the basis of recent population-based data. The discrepancy might be due to the changing nutritional habits. Causes of death included acute kidney injury, chronic kidney disease, and stroke. The disease was highly recurrent in 9 of 11 (88.1%). Recurrences were observed 1 to 30 years after the first attack. Mean age at death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, the latter group will experience morbidity and mortality of the disease where rich, well-educated people can achieve prevention. The theory also explains why gout disappeared from the Vatican palaces but increased in the general population (De Santo et al, 2021a , b , 2022 ). We are certain that the use of salt in the papal kitchen is no longer what it once was in the past.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the latter group will experience morbidity and mortality of the disease where rich, well-educated people can achieve prevention. The theory also explains why gout disappeared from the Vatican palaces but increased in the general population (De Santo et al, 2021a , b , 2022 ). We are certain that the use of salt in the papal kitchen is no longer what it once was in the past.…”
Section: Discussionmentioning
confidence: 98%
“…Of note is the principal cause of kidney disease as obstructive nephropathy due to gout or stones. It has been shown that many popes suffered of kidney stone disease of gouty and non gouty origin, the former was more frequent (De Santo et al, 2021a , b ), however the last gouty pope was Pius X who died in 1914. Thus in the last hundred year no pope was gouty indicating that gout is no longer a diseases of wealthy people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation